Increased neural response to social rejection in major depression. Issue 11 (20th June 2017) - Kumar, Poornima; Waiter, Gordon D; Dubois, Magda; Milders, Maarten; Reid, Ian; Steele, J Douglas
Abstract : Background: Being a part of community is critical for survival and individuals with major depressive disorder (MDD) have a greater sensitivity to interpersonal stress that makes them vulnerable to future episodes. Social rejection is a critical risk factor for depression and it is said to increase interpersonal stress and thereby impairing social functioning. It is therefore critical to understand the neural correlates of social rejection in MDD. Methods: To this end, we scanned 15 medicated MDD and 17 healthy individuals during a modified cyberball passing game, where participants were exposed to increasing levels of social exclusion. Neural responses to increasing social exclusion were investigated and compared between groups. Results: We showed that compared to controls, MDD individuals exhibited greater amygdala, insula, and ventrolateral prefrontal cortex activation to increasing social exclusion and this correlated negatively with hedonic tone and self‐esteem scores across all participants. Conclusions: These preliminary results support the hypothesis that depression is associated with hyperactive response to social rejection. These findings highlight the importance of studying social interactions in depression, as they often lead to social withdrawal and isolation.